IMPROVING STUDENT’S SPEAKING SKILL BY USING BRAINSTORMING METHOD OF THE TENTH GRADE IN SMA UNGGULAN UMMU RAHMAH IN 2020/2021 - Siti Aminah Hasibuan (FKIP Universitas Al Washliyah Medan, 2021)
The difficulty of students in speaking in English is a problem that must be solved. So this is the background for doing this research. The purpose of this study was to determine the effect of using the brainstorming method in students' speaking learning and to find out whether students are interested in learning with this method. The subjects in this study were students of the first grade of SMA Unggulan Ummu Rahmah for the academic year 2020/2021, totaling 30 students. This study used two classes, namely class X-1 as the experimental class and class X-2 as the control class. This study uses quantitative methods conducted by experimental research. Researchers used two instruments. There are tests carried out including pre-test, post-test and interviews. Based on the results of data processing, the results can be concluded that there is a significant increase, namely the post-test average value is higher than the pre-test (74.3>55) and (51.6>63.3). From the results of the data that has changed, it can be concluded that students have increased in learning by using the brainstorming method. And the results of interviews conducted with English teachers prove that this method is effective for students. The reliability of the research in this study showed the number 4.8. And this belongs to the good category and it can be said that this research is valid and significant